Book Reviews - Sutherland, John F.; Lewis, Thomas T.; Swain, Martha H.; Joyce, Davis D.; Sokolow, James A.; O'Toole, Thomas; Kuzirian, Eugene E.; Schmeller, Helmut J.; Davis, Clarence B.; Susskind, Jacob L.; Downard, William L.; Morrison, Larry R.; et al. (Teaching History: A Journal of Methods, 1981)
James Stuart Olsen. The Ethnic Dimension in American History. New York: St. Martin's Press, 1979. Pp. xxv, 440:- Cloth, $14.95; paper, $7.95; A. C. Hepburn, ed. Minorities in History. New York: St. Martin's Press, 1979. Pp. 251 . Cloth, $27.50. Review by John F. Sutherland of Manchester (Connecticut) Community College. David Burner, Eugene Genovese, and Forrest McDonald. The American People. St. James, New York: Revisionary Press, 1980. Cloth, $20.95; paper, $16.95. Review by Thomas T. Lewis of Mount Senario College. Richard E. Beringer. Historical Analysis: Contemporary Approaches to Clio's Craft. New York: John Wiley and Sonds, 1978. Pp. xii, 317. Paper, $12.95. Review by Martha H. Swain of Texas Woman's University. John T. Marcus. Sub Specie Historiae: Essays in the Manifestation of Historical and Moral Consciousness. Cranbury, New Jersey: Associated University Presses, 1980. Pp. 325. Cloth, $22.50. Review by David D. Joyce of The University of Tulsa. A. K. Dickinson and P. J. Lee. History Teaching and Historical Understanding. Exeter, New Hampshire: Heinemann Educational Books, Inc., 1978 . Pp. viii, 176. Paper, $10.95. Review by Jayme A. Sokolow of Texas Tech University. Richard W. Hull. Modern Africa: Change and Continuity. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1980. Pp. xii, 274. Paper, $9.95. Review by Thomas O'Toole of Western Carolina University. Clayton Roberts and David Roberts. A History of England. 2 volumes. Englewood Cliffs, New Jersey: Prentice-Hall, 1980. Pp. 891. Paper, $13.95 per volume. Review by Eugene E. Kuzirian of The University of Texas at El Paso. Alex de Jonge. The Weimar Chronicle: Prelude to Hitler. New York: New American Library, 1978 . Pp . 256 . Paper, $5.95. Review by Helmut J. Schmeller of Fort Hays State University. A. J. P. Taylor. The War Lords. New York: Penguin Books, 1976. Pp. 189. Paper, $3.95. Review by Clarence B. Davis of The College of Charleston. History Broadsheets. Exeter, New Hampshire: Heinemann Educational Books, 1978, 1979. $5.00 per packet. Review by Jacob L. Susskind of The Pennsylvania State University/ The Capitol Campus. Robert L. Heilbroner. The Economic Transformation of America. New York: Harcourt, Brace, Jovanovich, 1977. Pp. 276. Paper, $9.95; Henry C. Dethloff. Americans and Free Enterprise. Englewood Cliffs, New Jersey: Prentice-Hall, 1979. Pp, 336. Cloth, $13.95; Susan Previant Lee and Peter Passell. A New Economic View of American History. New York: W. W. Norton, 1979. Pp. 410. Cloth, $18.95; paper, $9.95; Martin L. Primack and James F. Willis. An Economic History of the United States. Menlo Park, Carlifornia: The Benjamin Cummings Publishing Company, 1980. Pp. 462. Cloth. $16.95. Review by William L. Downard of Saint Joseph's College, Indiana. John Chester Miller. The Wolf by the Ears: Thomas Jefferson and Slavery. New York: New American Library, 1977. Pp. xiv, 323. Paper, $5.95. Review by Larry R. Morrison of Virginia Polytechnic Institute & State University. Edmund Morris. The Rise of Theodore Roosevelt. New York: Ballantine Books, 1979. Pp. 886. Paper, $8.95. Review by Marvin Reed of Collegeville, Pennsylvania. Ellis W. Hawley. The Great War and the Search for Modern Order: A History of the American People and Their Institutions, 1917-1933. New York: St. Martin's Press, 1979. Pp. xvi, 264. Cloth, $12.95; paper, $4.95; Gerald D. Nash. The Great Depression and World War II: Organizaing America, 1933-1945. New York: St. Martin's Press, 1980. Pp. xvi, 1976. Clotch, $12.95; paper, $4.95. Review by Howard W. Smith of Spring Hill College. William L. Griffen and John Marciano. Teaching the Vietnam War. Montclair, New Jersey: Allanheld, Osmun, 1979. Pp. xx, 183. Paper, $6.50. Review by Frank J. Rader of SUNY Empire State College. Michael V. Namorato, ed. Have We Overcome? Race Relations Since Brown. Jackson, Mississippi: University Press Of Mississippi, 1979. Pp. xix, 232. Cloth, $15.00; paper, $7.95. Review by Gary J. Hunter of Glassboro State College.